Evaluation of allogeneic freeze-dried platelet lysate and conditioned serum in joint tissues under inflammatory condition in vitro - Camargo Garbin, Livia, author; Frisbie, David D., advisor; McIlwraith, C. Wayne, committee member; Kisiday, John D., committee member; Olver, Christine S., committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: autologous conditioned serum; freeze-dried; platelet-rich plasma; equine; allogeneic; osteoarthritis